Macroeconomics and health investing in health for economic development : report of the Commission on Macroeconomics and Health. - ebrary, Inc. (Geneva : World Health Organization, 2001)
The World Health Organization (WHO) presents the December 20, 2001 Commission on Macroeconomics and Health (CMH) report "Macroeconomics and Health: Investing in Health for Economic Development." The report is available in both PDF and HTML formats. The CMH emphasizes the importance of improving the health of the world's poor in order to improve the economic situation of all countries.
Electronic reproduction.
Keywords: World Health Organization. Commission on Macroeconomics and Health; Medical economics; Poor -- Health and hygiene; World health; Developing countries -- Economic conditions; Electronic books